PENGARUH CURRENT RATIO, TOTAL ASSET TURNOVER, DAN KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN YANG DIMEDIASI OLEH RETURN ON ASSET (Studi Kasus Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di BEI Periode 2018-2022) - Yoyon Dwi Cahyono; Dwi Nita Aryani (JURNAL LENTERA BISNIS, 2024)
This study was conducted to examine the effect of Current ratio (CR), Total Asset Turn Over (TATO), Enviromental Performance (EP) on Firm Value (PBV) mediated by profitability (ROA). The samples of this study were 19 food and beverage sub-sector manufacturing companies listed on the IDX in the 2018-2022 period. With the total data studied as many as 95 company years. The main data source in this study is the annual report. The data processing application uses Smart PLS. The results showed that Current ratio is able to have a significant effect on profitability, Total asset turnover is unable to have a significant effect on profitability, Environmental performance is able to have a significant effect on profitability, Profitability is able to have a significant effect on firm value, Current ratio is able to have a significant effect on firm value, Total asset turnover is unable to have a significant effect on firm value, Environmental performance is unable to have a significant effect on firm value, and Profitability is unable to significantly mediate the effect of Current ratio, Total asset turnover, and Environmental performance on firm value. Keywords: Current Ratio, Total Asset Turnover, Environmental Performance, Profitability, Firm Value.